A method for preparing Na2FePO4F / C material using ferric phosphate waste residue

The preparation of aluminum-doped Na2FePO4F/C materials through oxidative calcination and acidic reducing agent reaction has solved the problems of cumbersome processes and high production costs in the prior art, and achieved high magnification and high circulation performance material preparation.

CN119461308BActive Publication Date: 2025-04-04MILUO SHUNHUA LITHIUM IND CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510058776.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-04
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

When the prior art uses iron phosphate waste slag to prepare carbon-coated sodium ferrophosphate material, the process is cumbersome, the production cost is high, and the rate performance and circulation performance of the material still have room for improvement.

Method used

The aluminum-doped Na2FePO4F/C material is prepared by oxidative calcination pretreatment and acidic reducing agent reaction, which simplifies the process, reduces production costs, and improves the cyclic performance of the material through aluminum doping modification.

Benefits of technology

The preparation of Na2FePO4F/C material with simple process and low production cost is achieved. The material has excellent cycling performance at high magnification, good chemical uniformity, fine particles and high purity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461308B_ABST
    Figure CN119461308B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing Na2FePO4F / C material by using waste ferric phosphate residue, comprising the following steps: (1) pre-treating the waste ferric phosphate residue by oxidation roasting to obtain a roasting product; (2) mixing the roasting product with an acidic reducing agent to obtain a reaction product; (3) mixing the reaction product, a sodium source, a fluorine source, a carbon source, an iron source, a phosphorus source, and an aluminum source to react, and then drying the reaction product to obtain an intermediate product; (4) performing reduction roasting on the intermediate product to obtain Na2FePO4F / C. The present invention effectively improves the cycle performance of Na2FePO4F / C at a high rate by making full use of the doping and modification effect of aluminum impurities in the raw materials on the Na2FePO4F / C material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials, and in particular relates to a method for preparing a sodium battery positive electrode. Background Art

[0002] Given that the average service life of lithium iron phosphate batteries is about 6-8 years, a large number of retired lithium iron phosphate batteries will be produced. At present, the recycling technology of retired lithium iron phosphate batteries is relatively mature, and the lithium recovery rate is very high, reaching more than 90%. However, these technologies produce up to 5 tons of iron phosphate waste slag for every ton of lithium carbonate products produced. The large-scale storage of these iron phosphate waste slags not only poses a serious risk of environmental pollution, but also causes a huge waste of resources such as iron and phosphorus.

[0003] A lot of research has been conducted on the safe disposal and resource utilization of iron phosphate waste, and the main technical ideas are in two aspects:

[0004] First, through acid or alkali dissolution, purification and impurity removal, recrystallization and other processes, high-purity iron phosphate and other products are obtained, such as Chinese patent applications: CN116588909A, CN117623259A, CN116924363A, etc. However, these treatment methods generally have problems such as cumbersome process steps and high acid and alkali consumption, and the high-value utilization of iron phosphate slag has not been achieved.

[0005] Second, high-value materials are prepared using iron phosphate slag as raw material. This method is significantly better than the aforementioned method. For example, Chinese patent application CN114242968A discloses a carbon-coated sodium iron fluorophosphate material and its preparation method and application. It uses waste iron phosphate as raw material, mixes it with sodium fluoride and sodium carbonate, adds glucose, and ball-mills to obtain a mixture precursor powder; the mixture precursor powder is tableted, calcined, and naturally cooled to room temperature to obtain a mixture pre-burned precursor; the pre-burned mixture precursor is ball-milled to obtain a secondary ball-milled mixture precursor; the secondary ball-milled mixture precursor is tableted, calcined, and naturally cooled to room temperature to obtain a carbon-coated sodium iron fluorophosphate material. This method not only solves the problem of safe disposal of iron phosphate slag, but also realizes the high-value utilization of iron and phosphorus resources therein. However, the rate performance of the sodium iron fluorophosphate prepared by this process (43.8mAhg at 5C rate) is -1 There is still room for improvement in the discharge specific capacity) and cycle performance (1800 cycles at 5C rate, capacity retention rate is 86.3%). In addition, the process adopts secondary ball milling and secondary calcination, the process is cumbersome, the production loss is large, and the production cost is high.

[0006] Therefore, providing a carbon-coated sodium ferrophosphate material with a simple process, low production cost, and high rate and high cycle performance prepared from waste ferrophosphate slag is of great significance for the high-value utilization of waste ferrophosphate slag. Summary of the invention

[0007] The technical problem to be solved by the present invention is to overcome the shortcomings and defects mentioned in the above background technology and provide a method for preparing Na2FePO4F / C material using iron phosphate waste slag. The aluminum-doped Na2FePO4F / C prepared by this method has excellent cycle performance at high rate, and the preparation process is simple and the production cost is low.

[0008] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0009] A method for preparing Na2FePO4F / C material using ferric phosphate waste residue comprises the following steps:

[0010] (1) pre-treating the iron phosphate waste slag by oxidative roasting to obtain a roasting product;

[0011] (2) mixing the calcined product with an acidic reducing agent to obtain a reaction product;

[0012] (3) mixing the reaction product, a sodium source, a fluorine source, a carbon source, an iron source, a phosphorus source, and an aluminum source for reaction, and then drying the reaction product to obtain an intermediate product; after the reaction product, the sodium source, the fluorine source, the carbon source, the iron source, the phosphorus source, and the aluminum source are mixed, the raw materials are controlled to satisfy the following conditions: the molar ratio of Na, Fe, and P is (1.92-2.2):1:(0.98-1.05); the molar ratio of F and Fe is (0.90-1.02):1; the molar ratio of C and Fe is (0.25-1):1; the molar ratio of Al and Fe is (0.005-0.1):1;

[0013] (4) The intermediate product is subjected to reduction roasting to obtain Na2FePO4F / C.

[0014] In the present invention, if the iron and phosphorus elements in the iron phosphate waste slag meet the molar ratio of 1: (0.98-1.05), then there is no need to add an iron source or a phosphorus source during batching, otherwise an additional iron source or a phosphorus source is added so that the iron and phosphorus elements in the intermediate product of step (3) meet the molar ratio requirement of (1: 0.98-1.05). The present invention uses one or two of lithium iron phosphate acid leached lithium slag and / or lithium manganese iron phosphate acid leached lithium slag as raw materials, because they contain a certain amount of aluminum element, thereby reducing the amount of external aluminum source, or even no additional aluminum source is added. Specifically, if the molar ratio of Al to Fe in the iron phosphate waste slag is (0.005-0.1): 1, then there is no need to add an aluminum source during batching, otherwise an additional aluminum source is added so that the molar ratio of Al to Fe in the intermediate product of step (3) meets the requirement of (0.005-0.1): 1.

[0015] In the above method for preparing Na2FePO4F / C material using ferric phosphate waste slag, preferably, the ferric phosphate waste slag is lithium iron phosphate acid-leached lithium slag and / or lithium manganese iron phosphate acid-leached lithium slag, and the slag contains aluminum.

[0016] In the above method for preparing Na2FePO4F / C material using ferric phosphate waste slag, preferably, the oxidative roasting pretreatment is carried out under oxygen or air, the roasting temperature is controlled to be 150-900°C, and the reaction time is ≥10min.

[0017] The main function of the roasting process is to convert the metallic aluminum in the iron phosphate waste slag into aluminum oxide that is easily soluble in the subsequent process, which is beneficial to the doping of aluminum in the waste slag and solves the problem of aluminum doping. To this end, the iron phosphate waste slag should be pre-treated by oxidative roasting. In order to ensure the effect of the roasting treatment, it is further preferred that the roasting temperature is 400-750°C, which can effectively play the role of the roasting pre-treatment.

[0018] In the above method for preparing Na2FePO4F / C material using ferric phosphate waste, preferably, the acidic reducing agent includes one or more of oxalic acid, citric acid, hypophosphorous acid, formic acid, sulfurous acid and ascorbic acid; the molar ratio of the amount of the acidic reducing agent to the iron element in the ferric phosphate waste is (2-6): 1; the roasted product is mixed with the acidic reducing agent for reaction, and the reaction temperature is controlled to be ≥30°C and the reaction time is ≥15min. More preferably, the reaction temperature is controlled to be ≥50°C and the reaction time is ≥30min. The Fe in the ferric phosphate waste is in a high-valent state, while the iron in the target product sodium ferrous fluorophosphate is divalent. The present invention converts the iron source into a target low-valent state by reacting the oxidative roasted product with the acidic reducing agent, and fully disperses the aluminum element to utilize the impurity element aluminum in the raw material in situ. Too much reducing agent may result in metallic iron. If the amount of reducing agent is insufficient, the presence of high-valent iron will lead to the presence of impurity phases in subsequent products, affecting the subsequent electrochemical performance. Controlling the reaction temperature and reaction time can ensure the reaction effect and the electrochemical performance of subsequent products.

[0019] In the above-mentioned method for preparing Na2FePO4F / C material using ferric phosphate waste, preferably, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide and sodium acetate; the fluorine source includes sodium fluoride; the carbon source includes at least one of glucose, sucrose, polyethylene glycol and starch; the iron source includes at least one of red iron oxide, ferrous oxalate, ferrous sulfate, ferric acetate, ferric nitrate and ferrous citrate; the phosphorus source includes at least one of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate and sodium phosphate; the aluminum source includes at least one of aluminum nitrate, aluminum oxide and aluminum phosphate.

[0020] In the above method for preparing Na2FePO4F / C material using ferric phosphate waste, preferably, when the reaction product, sodium source, fluorine source, carbon source, iron source, phosphorus source and aluminum source are mixed for reaction, the reaction temperature is controlled to be ≥30°C and the reaction time is ≥30min. More preferably, the reaction temperature is controlled to be ≥50°C and the reaction time is ≥60min. The control of the above reaction process parameters can ensure the electrochemical performance of subsequent products.

[0021] In the above method for preparing Na2FePO4F / C material using ferric phosphate waste residue, preferably, the drying temperature is controlled to be ≥70°C and the reaction time is ≥6h during drying. Drying is carried out by one or more of spray drying, rotary kiln, tunnel kiln, muffle furnace, tubular furnace, electric furnace and oven drying.

[0022] In the above method for preparing Na2FePO4F / C material using ferric phosphate waste, preferably, when the intermediate product is subjected to reduction roasting, the roasting temperature is controlled to be 200-850°C and the roasting time is 2-20h. More preferably, the reduction roasting adopts a two-stage roasting process, first roasting at 300-700°C for 3-15h, and then roasting at 550-770°C for 2-10h. The control of the above roasting process parameters ensures that the generated products are all sodium ferrous fluorophosphate without containing other impurity peaks, which can ensure the electrochemical performance of subsequent products.

[0023] In the above method for preparing Na2FePO4F / C material using ferric phosphate waste, preferably, when the roasted product is mixed with the reducing agent for reaction, the roasted product is slurried with a solvent, and then the reducing agent is added to react to obtain reaction system one; the sodium source, fluorine source, carbon source, iron source, phosphorus source, and aluminum source are slurried with a solvent to obtain reaction system two; the solvent is one or two of water or ethanol; the reaction product, sodium source, fluorine source, carbon source, iron source, phosphorus source, and aluminum source are mixed to react to react the reaction system one and the reaction system two. The Na2FePO4F / C positive electrode material prepared by the above preparation method has good chemical uniformity, fine particles, high purity, simple equipment, low cost, easy doping with trace elements, and can achieve uniform doping at the molecular level, and there is no need to adjust the pH of the solution during the process.

[0024] The present invention is a method for preparing high-performance Na2FePO4F / C materials using waste ferric phosphate residues. The key to the technology is: first, the raw materials are mixed in the solution to achieve highly uniform dispersion of the materials and molecular-level mixing, which is conducive to the preparation of fine-grained and uniform Na2FePO4F / C materials, creating good conditions for subsequent electrochemical performance improvement. Second, based on our latest research results, the present invention utilizes Al 3+ Na2FePO4F was modified by doping with Al 3+ Replace Fe in the lattice 2+The position of the aluminum ions is optimized, the diffusion rate of sodium ions is increased (the diffusion coefficient is increased by about 1 order of magnitude), and the cycle performance of the Na2FePO4F cathode material is effectively improved, especially the cycle stability at high rates is also improved. Third, in order to facilitate the preparation of high-performance aluminum-doped Na2FePO4F / C materials from iron phosphate waste slag, the present invention uses oxidative roasting pretreatment and acidic reducing agent reaction, and the two work synergistically to achieve the raw material Fe 3+ The reduction transformation changes the existence form of aluminum in the ferrophosphate waste slag, for example, converts metallic aluminum into aluminum ions, providing the basic conditions for aluminum doping.

[0025] The present invention is based on the concept of "treating waste with waste", uses low-cost lithium iron phosphate acid leaching lithium slag and / or lithium manganese iron phosphate acid leaching lithium slag as raw materials and glucose as a carbon coating agent to prepare carbon-coated Na2FePO4F, avoiding high-cost iron salts, phosphates and carbon coating agents, which is beneficial to environmental protection and cost reduction.

[0026] Compared with the prior art, the advantages of the present invention are:

[0027] The method for preparing Na2FePO4F / C material by using ferric phosphate waste residue of the present invention has good chemical uniformity, fine particles, high purity, simple equipment, low cost, easy doping of trace elements, and realizes uniform doping at the molecular level. The operation is simple and the material loss in the process is small. By making full use of the doping and modification effect of aluminum impurities in the raw materials on the Na2FePO4F / C material, the cycle performance of Na2FePO4F / C at high rate is effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 It is the Na2FePO4F / C rate curve diagram prepared in the examples and comparative examples.

[0030] Figure 2 It is a long cycle curve diagram of Na2FePO4F / C prepared in the examples and comparative examples at a rate of 0.5C. DETAILED DESCRIPTION

[0031] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0032] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0033] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0034] Embodiment 1:

[0035] A method for preparing Na2FePO4F / C material using ferric phosphate waste residue comprises the following steps:

[0036] (1) Oxidatively roast the iron phosphate slag; in air, control the roasting temperature to 600°C and the reaction time to 60 minutes. The iron phosphate waste slag is lithium iron phosphate acid leaching lithium slag, which contains aluminum, and the molar ratio of Al to Fe is 0.008:1, and the molar ratio of Fe to P is 1:1. No aluminum source needs to be added subsequently.

[0037] (2) Add water to the calcined iron phosphate slag obtained in step (1) to prepare slurry.

[0038] (3) Adding an acidic reducing agent to step (2) to carry out a reaction; the reducing agent is oxalic acid, the reaction temperature is controlled to be 50° C., and the reaction time is 30 min; the molar ratio of the reducing agent to the iron element is 3:1.

[0039] (4) Add a sodium source (sodium hydroxide), a fluorine source (sodium fluoride), and a carbon source (glucose) into water to prepare pulp.

[0040] (5) The reaction product obtained in step (3) and the slurry obtained in step (4) are mixed for reaction, wherein the molar ratio of Na, Fe and P in the mixed slurry is 2.02:1:1, the molar ratio of the fluorine source to the Fe in the mixed slurry is 1:1, and the molar ratio of the carbon source to the Fe in the mixed slurry is 0.5:1; the reaction temperature is controlled to be 50° C. and the reaction time is 60 min.

[0041] (6) Dry the product obtained in step (5) at a temperature of 80°C for 12 h.

[0042] (7) The product obtained in step (6) is calcined, wherein the material is first calcined at 350° C. for 4 h and then calcined at 650° C. for 6 h to obtain a carbon-coated aluminum-doped Na2FePO4F / C positive electrode material.

[0043] Embodiment 2:

[0044] A method for preparing Na2FePO4F / C material using ferric phosphate waste residue comprises the following steps:

[0045] (1) Oxidative roasting of iron phosphate slag; in air, the roasting temperature is controlled to be 400°C and the reaction time is 200 min. The iron phosphate waste slag is lithium iron phosphate acid leaching lithium slag, which contains aluminum, and the molar ratio of Al to Fe is 0.002:1, and the molar ratio of Fe to P is 1:1.01. Aluminum source needs to be added later.

[0046] (2) Add water to the calcined iron phosphate slag obtained in step (1) to prepare slurry.

[0047] (3) Adding an acidic reducing agent to step (2) to carry out a reaction; the reducing agent is oxalic acid, the reaction temperature is controlled to be 50° C., and the reaction time is 30 min; the molar ratio of the reducing agent to the iron element is 2.5:1.

[0048] (4) Add a sodium source (sodium hydroxide and sodium carbonate, with a mass ratio of 1:1), a fluorine source (sodium fluoride), a carbon source (glucose), and an aluminum source (aluminum nitrate) into water to prepare pulp.

[0049] (5) The reaction product obtained in step (3) and the slurry obtained in step (4) are mixed for reaction, wherein the molar ratio of Na, Fe and P in the mixed slurry is 2.10:1:1.01, the molar ratio of the fluorine source to the Fe in the mixed slurry is 1.01:1, the molar ratio of the carbon source to the Fe in the mixed slurry is 0.75:1, and the molar ratio of the aluminum source to the Fe in the mixed slurry is 0.040:1; the reaction temperature is controlled to be 80°C and the reaction time is 90 min.

[0050] (6) Dry the product obtained in step (5) at a temperature of 80°C for 12 h.

[0051] (7) The product obtained in step (6) is calcined, wherein the material is first calcined at 300°C for 7 hours and then calcined at 650°C for 6 hours to obtain a carbon-coated aluminum-doped Na2FePO4F / C positive electrode material.

[0052] Embodiment 3:

[0053] A method for preparing Na2FePO4F / C material using ferric phosphate waste residue comprises the following steps:

[0054] (1) Oxidatively roasting the iron phosphate slag; in air, the roasting temperature is controlled to be 700°C and the reaction time is 30 minutes. The iron phosphate waste slag is lithium iron phosphate acid leaching lithium slag, which contains aluminum, and the molar ratio of Al to Fe is 0.095:1, and the molar ratio of Fe to P is 1:1.02. No aluminum source needs to be added subsequently.

[0055] (2) Adding alcohol to the calcined iron phosphate slag obtained in step (1) to prepare pulp.

[0056] (3) Adding an acidic reducing agent to step (2) to carry out a reaction; the reducing agent is citric acid, the reaction temperature is controlled to be 50° C., and the reaction time is 30 min; the molar ratio of the reducing agent to the iron element is 2:1.

[0057] (4) Add a sodium source (sodium hydroxide), a fluorine source (sodium fluoride), and a carbon source (glucose) into water to prepare pulp.

[0058] (5) The reaction product obtained in step (3) and the slurry obtained in step (4) are mixed for reaction, wherein the molar ratio of Na, Fe and P in the mixed slurry is 2.05:1:1.02, the molar ratio of the fluorine source to the Fe in the mixed slurry is 1.01:1, and the molar ratio of the carbon source to the Fe in the mixed slurry is 0.90:1; the reaction temperature is controlled to be 60° C. and the reaction time is 90 min.

[0059] (6) Dry the product obtained in step (5) at a temperature of 90°C for 8 hours.

[0060] (7) The product obtained in step (6) is calcined, wherein the material is first calcined at 650° C. for 10 h and then calcined at 720° C. for 3 h to obtain a carbon-coated aluminum-doped Na2FePO4F / C positive electrode material.

[0061] Comparative Example 1:

[0062] A method for preparing Na2FePO4F / C material using ferric phosphate waste residue comprises the following steps:

[0063] (1) Without oxidation roasting, the iron phosphate slag is directly slurried by adding water. The iron phosphate waste slag is the lithium phosphate acid leaching slag, which contains aluminum, and the molar ratio of Al to Fe is 0.008:1, and the molar ratio of Fe to P is 1:1. No aluminum source is added subsequently.

[0064] (2) adding an acidic reducing agent to step (1) to carry out a reaction; the reducing agent is oxalic acid, the reaction temperature is controlled to be 50° C., and the reaction time is 30 min; the molar ratio of the reducing agent to the iron element is 3:1.

[0065] (3) Add a sodium source (sodium hydroxide), a fluorine source (sodium fluoride), and a carbon source (glucose) into water to prepare pulp.

[0066] (4) The reaction product obtained in step (2) and the slurry obtained in step (3) are mixed for reaction, wherein the molar ratio of Na, Fe and P in the mixed slurry is 2.02:1:1, the molar ratio of the fluorine source to the Fe in the mixed slurry is 1:1, and the molar ratio of the carbon source to the Fe in the mixed slurry is 0.5:1; the reaction temperature is controlled to be 50° C. and the reaction time is 60 min.

[0067] (5) Dry the product obtained in step (4) at a temperature of 80°C for 12 h.

[0068] (6) The product obtained in step (5) is calcined, wherein the material is first calcined at 350° C. for 4 h and then calcined at 650° C. for 6 h to obtain a carbon-coated Na2FePO4F / C positive electrode material.

[0069] Comparative Example 2:

[0070] A method for preparing Na2FePO4F / C material using ferric phosphate waste residue comprises the following steps:

[0071] (1) Oxidatively roasting the iron phosphate slag; in air, the roasting temperature is controlled to be 600°C and the reaction time is 60 minutes. The iron phosphate waste slag is lithium iron phosphate acid leaching lithium slag, which contains aluminum, and the molar ratio of Al to Fe is 0.008:1, and the molar ratio of Fe to P is 1:1, and no aluminum source is added subsequently.

[0072] (2) Add water to the calcined iron phosphate slag obtained in step (1) to prepare slurry.

[0073] (3) Add a sodium source (sodium hydroxide), a fluorine source (sodium fluoride), and a carbon source (glucose) into water to prepare pulp.

[0074] (4) The reaction product obtained in step (2) and the slurry obtained in step (3) are mixed for reaction, wherein the molar ratio of Na, Fe and P in the mixed slurry is 2.02:1:1, the molar ratio of the fluorine source to the Fe in the mixed slurry is 1:1, and the molar ratio of the carbon source to the Fe in the mixed slurry is 0.5:1; the reaction temperature is controlled to be 50° C. and the reaction time is 60 min.

[0075] (5) Dry the product obtained in step (4) at a temperature of 80°C for 12 h.

[0076] (6) The product obtained in step (5) is calcined, wherein the material is first calcined at 350° C. for 4 h and then calcined at 650° C. for 6 h to obtain a carbon-coated Na2FePO4F / C positive electrode material.

[0077] The performance of the positive electrode materials in the above examples 1-3 and comparative examples 1-2 was tested. Figure 1 As shown, the rate performance of the Na2FePO4F / C positive electrode material prepared in Example 1-3 at room temperature is much better than that of Comparative Example 1-2. The reversible performance of the charge-discharge cycle of the material at 0.5C rate at room temperature is as follows Figure 2 As shown, after 100 charge and discharge cycles, the capacity retention rates of Example 1, Example 2, and Example 3 are 92.75%, 91.25%, and 92.77%, respectively, while the capacity retention rates of Comparative Example 1 and Comparative Example 2 are only 77.46% and 70.32%, respectively.

Claims

1. A method for preparing Na2FePO4F / C material using ferric phosphate waste residue, characterized in that: The following steps are involved: (1) pre-treating the iron phosphate waste residue by oxidative roasting to obtain a roasting product; the iron phosphate waste residue contains aluminum; (2) mixing the calcined product with an acidic reducing agent to obtain a reaction product; (3) mixing the reaction product, a sodium source, a fluorine source, a carbon source, an iron source, a phosphorus source, and an aluminum source for reaction, and then drying the reaction product to obtain an intermediate product; after the reaction product, the sodium source, the fluorine source, the carbon source, the iron source, the phosphorus source, and the aluminum source are mixed, the raw materials are controlled to satisfy the following conditions: the molar ratio of Na, Fe, and P is (1.92-2.2):1:(0.98-1.05); the molar ratio of F and Fe is (0.90-1.02):1; the molar ratio of C and Fe is (0.25-1):1; the molar ratio of Al and Fe is (0.005-0.1):1; (4) The intermediate product is subjected to reduction roasting to obtain Na2FePO4F / C.

2. The method for preparing Na2FePO4F / C material using ferric phosphate waste residue according to claim 1, characterized in that: The iron phosphate waste residue is lithium iron phosphate acid-leached lithium residue and / or lithium manganese iron phosphate acid-leached lithium residue.

3. The method for preparing Na2FePO4F / C material using ferric phosphate waste residue according to claim 1, characterized in that: The oxidation roasting pretreatment is carried out under oxygen or air, the roasting temperature is controlled to be 150-900°C, and the reaction time is ≥10min.

4. The method for preparing Na2FePO4F / C material using ferric phosphate waste residue according to claim 1, characterized in that: The acidic reducing agent includes one or more of oxalic acid, citric acid, hypophosphorous acid, formic acid, sulfurous acid and ascorbic acid; the molar ratio of the acidic reducing agent to the iron element in the ferric phosphate waste is (2-6):1; the roasting product and the acidic reducing agent are mixed and reacted, and the reaction temperature is controlled to be ≥30°C and the reaction time is ≥15min.

5. The method for preparing Na2FePO4F / C material using ferric phosphate waste residue according to claim 1, characterized in that: The sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide and sodium acetate; the fluorine source includes sodium fluoride; the carbon source includes at least one of glucose, sucrose, polyethylene glycol and starch; the iron source includes at least one of red iron oxide, ferrous oxalate, ferrous sulfate, ferric acetate, ferric nitrate and ferrous citrate; the phosphorus source includes at least one of phosphoric acid, ammonium monohydrogen phosphate, ammonium dihydrogen phosphate, sodium monohydrogen phosphate, sodium dihydrogen phosphate and sodium phosphate; the aluminum source includes at least one of aluminum nitrate, aluminum oxide and aluminum phosphate.

6. The method for preparing Na2FePO4F / C material using ferric phosphate waste residue according to claim 1, characterized in that: When the reaction product, sodium source, fluorine source, carbon source, iron source, phosphorus source and aluminum source are mixed for reaction, the reaction temperature is controlled to be ≥30° C. and the reaction time is controlled to be ≥30 min.

7. The method for preparing Na2FePO4F / C material using ferric phosphate waste residue according to claim 1, characterized in that: When the intermediate product is subjected to reduction roasting, the roasting temperature is controlled to be 200-850° C. and the roasting time is 2-20 hours.

8. The method for preparing Na2FePO4F / C material using ferric phosphate waste residue according to claim 7, characterized in that: The reduction roasting adopts a two-stage roasting process, first roasting at 300-700°C for 3-15h, and then roasting at 550-770°C for 2-10h.

9. The method for preparing Na2FePO4F / C material using ferric phosphate waste residue according to claim 1, characterized in that: When the roasting product is mixed with a reducing agent for reaction, the roasting product is slurried with a solvent, and then the reducing agent is added to react to obtain reaction system one; a sodium source, a fluorine source, a carbon source, an iron source, a phosphorus source, and an aluminum source are slurried with a solvent to obtain reaction system two; the solvent is one or two of water or ethanol; the reaction product, the sodium source, the fluorine source, the carbon source, the iron source, the phosphorus source, and the aluminum source are mixed for reaction to obtain a mixed reaction of reaction system one and reaction system two.

Citation Information

Patent Citations

  • Method for preparing iron phosphate from ferrophosphorus slag obtained after lithium extraction of waste lithium iron phosphate

    CN116588909A

  • Method for recycling iron phosphate from ferrophosphorus waste residues

    CN116924363A

  • Method for recovering iron phosphate from waste lithium iron phosphate battery

    CN117623259A

  • Carbon-coated sodium ferric fluorophosphate material as well as preparation method and application thereof

    CN114242968A

  • Resource utilization method of waste lithium iron phosphate battery

    CN117712544A